Biodegradation of Chlorothalonil Fungicide in Coastal Areas of the Colombian Caribbean Suitable for Banana Crops - Betancourt Portela, Julián Mauricio; Bautista Duarte, Paola Andrea; Narváez Flórez, Silvia; Parra Lozano, Juan Pablo (TECCIENCIA, 2018)
Chlorothalonil (CHT) is a chlorinated-nitrogen fungicide used in the control of black sigatoka, a disease that affects banana and plantain, has adverse effects on the environment and its metabolites can be toxic. The CHT has been the object of several studies related to its behavior and degradation in the environment; however, few works have been developed in tropical areas, such as the case of the banana zone of Magdalena - Colombia. In addition, it is unknown if the microbial diversity existing in these soils can transform compounds such as CHT, thus these microorganisms can be the basis for the implementation of remediation strategies based on bioaugmentation. In this sense, the present study aims to evaluate the degradation of CHT in soils of a tropical coastal zone, under conditions of natural attenuation and bioaugmentation with native microorganisms. For this purpose, microorganisms capable of growing with CHT as their sole carbon source (10.8 mg.l -1 ) and tolerating a concentration up to 25 mg.l-1 were isolated and selected from soils in the Magdalena-Colombia banana zone. Subsequently, CHT degradation tests (2000 ng.g-1 ) were performed on experimental plots, with bioaugmentation of native microorganisms and natural attenuation during 35 days, evaluating the growth of microbial populations and the degradation of CHT by gas chromatography associated with a mass spectrometry detector (GC/MS). Because of the microbial selection process, 8 morphotypes were obtained with the ability to grow in CHT as the sole carbon source and tolerate concentrations up to 25 g.l -1 . The isolates were identified by sequencing the 16S rDNA gene as belonging to the genera Enterobacter, Klebsiella, Pseudomonas and Citrobacter. The CHT degradation tests showed that under bioaugmentation conditions with the native microorganisms selected in the study, a 100% reduction was achieved after 21 days; while under natural attenuation conditions after 35 days the degradation reached values of 98.5%. The application of bioaugmentation of selected and enhanced bacteria increased the rate of pesticide degradation by ~2.5 times, reducing the half-life from 6.2 to 2.5 days. The results demonstrated the effectiveness of the bioaugmentation treatment and that the selected consortium may be useful for bioremediation of banana crops soils contaminated with the fungicide.